(K, Na)NbO3-based piezoelectric single crystals: Growth methods, properties, and applications. Issue 8 (28th April 2020) - Koruza, Jurij; Liu, Hairui; Höfling, Marion; Zhang, Mao-Hua; Veber, Philippe
Abstract: Abstract : Piezoelectric single crystals based on the perovskite ferroelectric system (K, Na)NbO3 have been widely investigated over the past 20 years due to large piezoelectric coefficients, high transition temperatures, low density, and the nontoxic chemical composition. Various crystal growth methods were examined, including high-temperature solution growth, solid-state crystal growth, Bridgman–Stockbarger method, and the floating zone method. Increased understanding of the crystal growth process and post-growth treatments resulted in improved crystal quality and larger sizes. Recently, crystals with high piezoelectric and electromechanical coupling coefficients exceeding 1000 pC/N and 0.90, respectively, were reported. Moreover, their large potential for high-frequency ultrasonic medical imaging was demonstrated. This work provides a review of the development of piezoelectric (K, Na)NbO3 -based single crystals, including their growth, defect chemistry, domain structures, electromechanical properties, and applications. Approaches for reducing growth defects, controlling point defects, and domain engineering are discussed. The remaining open issues are presented and an outlook on the future is provided.